2018
DOI: 10.3389/fpsyg.2018.01809
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Measures Can Be Used as a Proxy for Language Dominance in Bilingual Language Acquisition Research

Abstract: Language dominance is a multidimensional construct comprising several distinct yet interrelated components, including language proficiency, exposure and use. The exact relation between these components remains unclear. Several studies have observed a (non-linear) relationship between bilingual children’s amount of exposure and absolute proficiency in each language, but our understanding of the relationship between language exposure and use and relative proficiency is limited. To address this question, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 59 publications
2
52
0
1
Order By: Relevance
“…Bedore et al (2012), Unsworth (2016) as well as Unsworth et al (2018) found that relative amount of exposure and use reliably predicted dominance group membership as determined by proficiency measures, confirming that relative amount of use and exposure can be used as a proxy for language dominance in bilingual children. For the purposes of the present study and building upon the findings of Bedore et al (2012), Unsworth (2016), and Unsworth et al (2018), we use experiential-based measures to establish language dominance for our participants and calculate this based on the information obtained by the PaBiQ as outlined in “The LITMUS-Questionnaire for Parents of Bilingual Children”.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…Bedore et al (2012), Unsworth (2016) as well as Unsworth et al (2018) found that relative amount of exposure and use reliably predicted dominance group membership as determined by proficiency measures, confirming that relative amount of use and exposure can be used as a proxy for language dominance in bilingual children. For the purposes of the present study and building upon the findings of Bedore et al (2012), Unsworth (2016), and Unsworth et al (2018), we use experiential-based measures to establish language dominance for our participants and calculate this based on the information obtained by the PaBiQ as outlined in “The LITMUS-Questionnaire for Parents of Bilingual Children”.…”
Section: Methodsmentioning
confidence: 54%
“…A number of methods have been put forward for measuring and operationalizing language dominance in bilingual children. These measures fall into two categories: performance-based measures and experiential-based measures (Unsworth, 2016; Unsworth et al, 2018). Estimates of language dominance obtained by performance-based measures are based on quantitative differences in proficiency measurements between the two languages of a bilingual.…”
Section: Methodsmentioning
confidence: 99%
“…This may be because the English-dominant Greek HL children in our study may avoid using these low frequency non-canonical structures and resort to canonical and unambiguous SVO sentences, as they enter the English mainstream school system and become more dominant in English. Provided that input is a good proxy for dominance (Unsworth, Chondrogianni, & Skarabela, 2018), the HL children in our sample were more dominant in Greek in early childhood than when we tested them at school age. For production, the opportunity to use the language on a daily basis gives rise to better case production, confirming previous findings in the bilingual literature that degree of current language use positively affects production skills (Bohman, Bedore, Peña, Mendez-Perez, & Gillam, 2010).…”
Section: Individual Differencesmentioning
confidence: 99%
“…The extent to which bilingual children are proficient in both of their languages has also been used as a predictor for the extent of cognitive advantages compared to monolingual children (e.g., Blom, Küntay, Messer, Verhagen & Leseman, 2014). Conversely, researchers have tried to explain children's (relative) language proficiency across development by looking at child-internal factors, such as age of acquisition, and child-external variables, such as amount of exposure (e.g., Bedore, Peña, Griffin & Hixon, 2016;Bedore, Peña, Summers, Boerger, Resendiz, Greene, Bohman & Gillam, 2012;Chondrogianni & Marinis, 2011;Hoff, Core, Place, Rumiche, Señor & Parra, 2012;Unsworth, Chondrogianni & Skarabela, 2018).…”
Section: Introductionmentioning
confidence: 99%